2021
DOI: 10.1007/s10856-021-06591-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo biological performance of hydroxyapatite from fish waste

Abstract: The aim of this study was to evaluate biocompatibility of hydroxyapatite (HAP) from fish waste using in vitro and in vivo assays. Fish samples (whitemouth croaker - Micropogonias furnieri) from the biowaste was used as HAP source. Pre-osteoblastic MC3T3-E1 cells were used in vitro study. In addition, bone defects were artificially created in rat calvaria and filled with HAP in vivo. The results demonstrated that HAP reduced cytotoxicity in pre-osteoblast cells after 3 and 6 days following HAP exposure. DNA con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Many other studies indicated an excellent biocompatibility of HA with bony tissue [ 10 , 35 , 38 , 42 , 43 , 44 ]. The biocompatibility of HA obtained from fish waste was also confirmed in vivo and in vitro in a study by Prado et al [ 37 ]. Giorno et al [ 38 ] stated that HA is a biomaterial whose rejection is only minimal or nonexistent.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Many other studies indicated an excellent biocompatibility of HA with bony tissue [ 10 , 35 , 38 , 42 , 43 , 44 ]. The biocompatibility of HA obtained from fish waste was also confirmed in vivo and in vitro in a study by Prado et al [ 37 ]. Giorno et al [ 38 ] stated that HA is a biomaterial whose rejection is only minimal or nonexistent.…”
Section: Discussionmentioning
confidence: 64%
“…HA is one of the widely and regularly used bioceramics for bone regeneration, which has been investigated due to its excellent biological properties, potential resorbability, moulding capabilities, and easy manipulation. The use of various types of HA was described in diverse scientific sources [ 37 , 42 ]. HA is characterised by excellent biocompatibility with bony tissue, high bioactivity, and osteoconductivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The micro-CT test and histological results showed that the calcined butterfish bone had a lower in vivo degradation rate. The low degradation rate of biological materials might increase the physical resistance to bone growth, affect the interaction with body fluids, and interfere with bone formation (da Silva Brum et al, 2019;Nazir and Iqbal, 2021;Prado et al, 2021). However, compared with Bio-Oss, the calcined butterfish bone also had certain advantages, such as its high porosity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, natural or synthetic hydroxyapatite (HA) is also known to have been used as an implant material for orthopedic and dental applications [4]. Hydroxyapatite (HAP) from fish bone waste reduces cytotoxicity in pre-osteoblast cells [5].…”
Section: Introductionmentioning
confidence: 99%